Anxiety, depression and impaired health-related quality of life in patients with occupational hand eczema - Böhm, Dana Katja; Diepgen, Thomas L. (Contact dermatitis, 2012)
Background. Occupational hand eczema is one of the most frequent occupational diseases. Few data about the prevalence of mental comorbidities are available. Objectives. We aimed to investigate the prevalence of anxiety, depression symptoms, the impairment of health-related quality of life (HRQoL) and their correlates in patients with occupational hand eczema. Patients and methods. A test battery consisting of the German versions of the Hospital Anxiety and Depression Scale, the Dermatology Life Quality Index (DLQI) as a specific instrument and the Short Form Health Survey-36 (SF-36) as a generic instrument for HRQoL was applied in 122 patients. The severity of hand eczema was assessed with the Osnabrueck Hand Eczema Severity Index (OHSI). Results. Twenty per cent of patients had a positive anxiety score, and 14% had a positive depression score. Higher anxiety levels, a greater impairment in the SF-36 mental component summary score and a higher DLQI category score for symptoms and feelings was detected in females than in males. The OHSI correlated with the impairment in HRQoL, and an association of severe hand eczema with symptoms of anxiety and depression was found in males. Conclusions. We found a high prevalence of anxiety and depression in our study population of patients with occupational hand eczema. Preventive measures should consider the psychosocial implications of occupational hand eczema.